CMAF – CHRIS Morphological Adaptive Filter - Kupidura, Przemysław (Ecological Questions, 2013)
The paper presents a new method of CHRIS images filtering. The presented algorithm is based on mathematical morphology operations and allows to correct the main CHRIS images noise types, like missing pixels and vertical stripes caused by a malfunctioning of the device. the algorithm is preceded by the brief discussion on the nature of the noise and the basis of mathematical morphology. The resulting images are compared to the results of application of other types of CHRIS-dedicated algorithms (Settle methods).